Clinical utility of the list sign as a predictor of non-demyelinating disorders in a multiple sclerosis (MS) practice. (3rd May 2016) - Anbarasan, Deepti; Campion, Gabriel; Campion, Paul; Howard, Jonathan
Abstract : Objectives: Not all patients referred for evaluation of multiple sclerosis (MS) meet criteria required for MS or related entities. Identification of markers to exclude demyelinating disease may help detect patients whose presenting symptoms are inconsistent with MS. In this study, we evaluate whether patients who present a self-prepared list of symptoms during an initial visit are less likely to have demyelinating disease and whether this action, which we term the "list sign, " may help exclude demyelinating disease. Methods: Using chart review, 300 consecutive new patients who presented for evaluation to a neurologist at a tertiary MS referral center were identified retrospectively. Patients were defined as having demyelinating disease if diagnosed with MS or a related demyelinating condition. Results: Of the 233 enrolled subjects, 157 were diagnosed with demyelinating disease and 74 did not meet criteria for demyelinating disease. Fifteen (8.4%) subjects had a positive list sign, of which 1 patient had demyelinating disease. The 15 subjects described a mean of 12.07 symptoms, and 8 of these patients met Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) criteria for somatic symptom disorder. The specificity and positive predictive value of the list sign for non-demyelinating disease were 0.99 (95% confidence interval (CI) 0.96–0.99) and 0.93 (95% CI 0.66–0.99), respectively. Conclusion: A positive list sign may be useful to exclude demyelinating disease and to guide diagnostic evaluations for other conditions. Patients with a positive list sign also have a high incidence of somatic symptom disorder.